Avaliação comparativa entre processos de secagem na produção de tomate em pó - Jorge, Aline (2014)
The general objective of this research was to achieve a comparative study among three drying processes applied to tomato dehydration, being two already usual in industrial processes and one is an innovatied on fruit and vegtables drying. For that was developed and tested a laboratory prototype of the hot air drying system and were defined the parameters and drying conditions for each drying system used for this study. The research developed in stages of: definition of the drying parameters, obtention of tomato powder and characterization of the tomato powder. Calculaitons performedtodetermine the energy consumption and operation costs for each system. The raw material used was characterized and the tomato powders obtained by each drying treatment performed. The determinations realized for the raw material and product obtained were moisture, ash, protein, fat, acidity, pH, water activity, total phenolic compounds, carotenes in fractios of β-carotene and lycopene, ascorbic acid and colour. According to the results was proven that the hot air drying, proposen as an innovativem, is able to dehydrate the tomatoes on the same way as the other with a reduced of time process, wich results in a significant reducing of costs and energy consumption, leading to productivity increase. Evaluating the centesimal composition was observed that de hot air drying system promoted minor degradation of the nutrients in tomato powder, highlighting the minor degradation of proteins, minor reducing of pH, major concentration of acidity ( in terms of citric acid), also presented de major increase on the concentration of the carotenes, both for β-carotene and lycopene.The lyofilization maintained the charcteristics of composition in the final product, although, showed the disadvantage of a high cost of the process, being largely highter than the others, did not present a good colour and did not reveal the increase on the concentration of the carotenes.The oven drying promoted the dehydration in a slightly longer time than the hot air flow; however, was the method that showed the major degradation on the final product obtained from all drying methods.